2017
DOI: 10.1128/aem.02548-16
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Evolutionary Trajectories Have Led to the Emergence of Races in Fusarium oxysporum f. sp. lycopersici

Abstract: Race 1 isolates of Fusarium oxysporum f. sp. lycopersici (FOL) are characterized by the presence of AVR1 in their genomes. The product of this gene, Avr1, triggers resistance in tomato cultivars carrying resistance gene I. In FOL race 2 and race 3 isolates, AVR1 is absent, and hence they are virulent on tomato cultivars carrying I. In this study, we analyzed an approximately 100-kb genomic fragment containing the AVR1 locus of FOL race 1 isolate 004 (FOL004) and compared it to the sequenced genome of FOL race … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 47 publications
1
43
1
2
Order By: Relevance
“…Moreover, it provides a means to escape “Muller’s ratchet” in mainly asexual species by exchanging at least parts of core chromosomes. The transposons that reside on pathogenicity chromosomes can play a role in fast adaptation to host-resistance, [19,74] probably mostly by mediating rearrangements [5,8,75], thus potentially disrupting modular genomic organizations and creating novel chromosome segments. Moreover, transposons may disperse into core chromosomes [76] where the chance of harmful effects of transposon insertion is larger than on dispensable chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it provides a means to escape “Muller’s ratchet” in mainly asexual species by exchanging at least parts of core chromosomes. The transposons that reside on pathogenicity chromosomes can play a role in fast adaptation to host-resistance, [19,74] probably mostly by mediating rearrangements [5,8,75], thus potentially disrupting modular genomic organizations and creating novel chromosome segments. Moreover, transposons may disperse into core chromosomes [76] where the chance of harmful effects of transposon insertion is larger than on dispensable chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of multiple almost identical sequences in a genome increases the likelihood of homologous recombination that can result in genome rearrangements or deletions [5], which can contribute to pathogen adaptation [1-3,6-15]. In addition, transposon insertion into an avirulence gene can result in regain of virulence [16-19]. If the avirulence gene is indispensable for infection the only option to escape recognition is to alter the amino acid sequence of the effector [20-22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that many other ff. spp., including Fol, have a polyphyletic origin 30 with some exhibiting clear patterns of 'race' evolution through stepwise loss of effectors 31 . All pathogenic Foc isolates formed a single clade, consistent with a single origin of pathogenicity on onion 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The 10 µL qPCR mixture contained 10 ng of gDNA, 10 pM of each primer, and 2 µL of HOT FirePolEvaGreen qPCR Mix Plus (Solis BioDyne; Tartu, Estonia) were performed in QuantStudioTM3 (Thermo Scientific; Walthamm MA, USA). The cycling program was set to 15 min at 95 • C, 40 cycles of 15s at 95 • C, 1 min at 60 • C, and 30s at 72 • C. The melting curve analysis was performed afterwards as follows: 15s at 95 • C, 1 min at 60 • C, and 15s at 95 • C. The sequences of the primers used are summarized in Table S1 [26,27]. For InterGenic Spacer (IGS) primers two standard curves (four-or ten-times dilution) were performed with a starting concentration of 10 ng, resulting with a primer efficiently of 110 and 95%, respectively.…”
Section: Analysis Of Fungal Colonization By Quantitative Pcrmentioning
confidence: 99%
“…Fo strains within the same vegetative compatibility group (VCG) can form stable heterokaryons, while those belonging to different VCGs undergo cell death upon heterokaryon formation [29]. To test whether VCG incompatibility can result in a reduced viable concentration of Fol4287, and thereby reduce disease symptoms, two Fol strains of different VCG (Fol4287 (VCG030) and Fol017 (VCG031), [26]) were coinoculated. This resulted in disease symptoms that were indistinguishable from those observed upon single inoculation ( Figure S1c).…”
Section: Endophyte-mediated Resistance Occurred At a 1:1 Ratio And Rementioning
confidence: 99%